2019
DOI: 10.1101/532366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact and evolutionary determinants of Neanderthal introgression on transcriptional and post-transcriptional regulation

Abstract: Archaic admixture is increasingly recognized as an important source of diversity in modern humans, with Neanderthal haplotypes covering 1-3% of the genome of present-day Eurasians. Recent work has shown that archaic introgression has contributed to human phenotypic diversity, mostly through the regulation of gene expression. Yet, the mechanisms through which archaic variants alter gene expression, and the forces driving the introgression landscape at regulatory regions remain elusive. Here, we explored the imp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…Petr et al used a direct f 4 ratio test to conclude that promoters and other conserved noncoding elements harbored less Neandertal DNA than the genome as a whole, but found no similar depletion in enhancers. However, a subsequent study by Silvert et al came to somewhat different conclusions using different methodology, which involved quantifying the distribution of alleles flagged as likely Neandertal in origin based on their presence in the Altai Neanderthal reference and their absence from an African reference panel [25].…”
Section: Introductionmentioning
confidence: 99%
“…Petr et al used a direct f 4 ratio test to conclude that promoters and other conserved noncoding elements harbored less Neandertal DNA than the genome as a whole, but found no similar depletion in enhancers. However, a subsequent study by Silvert et al came to somewhat different conclusions using different methodology, which involved quantifying the distribution of alleles flagged as likely Neandertal in origin based on their presence in the Altai Neanderthal reference and their absence from an African reference panel [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide association studies suggest that the DNA relics from this admixture left a phenotypic legacy, influencing, for example, skin and hair color, immune response, lipid metabolism, skull shape, bone morphology, blood coagulation, sleep patterns, and mood disorders ( Dannemann and Kelso, 2017 , Dannemann et al., 2016 , Gunz et al., 2019 , Khrameeva et al., 2014 , Quach et al., 2016 , Sams et al., 2016 , Sankararaman et al., 2014 , SIGMA Type 2 Diabetes Consortium et al., 2014 , Simonti et al., 2016 , Vernot and Akey, 2014 ). In addition, it has been reported that Neandertal-introgressed DNA has a significant effect on gene expression in adult human tissues possibly as a result of selection acting on Neandertal variants in regulatory regions ( Dannemann et al., 2017 , McCoy et al., 2017 , Petr et al., 2019 , Silvert et al., 2019 , Telis et al., 2019 ). However, these associations have been observed in living people or in tissues, where there is limited opportunity for controlled experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…The first link between archaic introgression and immunity was documented for the HLA region [47], some haplotypes of which seem to have been acquired by admixture with Neanderthals or Denisovans. Since these pioneering work, several studies, including ours, have reported immune-related genes for which archaic introgression has been beneficial [29,43,45,[48][49][50][51][52][53]. Some pertinent examples include the OAS1-3, STAT2, TLR6-1-10, and TNFAIP3 genes.…”
Section: The Adaptive Nature Of Introgression From Archaic Hominidsmentioning
confidence: 93%
“…Le premier lien entre introgression archaïque et immunité a été identifié dans la région HLA [47], dont certains haplotypes semblent avoir été acquis par métissage avec les Néandertaliens ou les Denisoviens. Depuis cette étude pionnière, plusieurs travaux, dont les nôtres, ont rapporté des gènes associés à l'immunité pour lesquels l'introgression archaïque s'est avérée bénéfique [29,43,45,[48][49][50][51][52][53]. Les gènes OAS1-3, STAT2, le cluster TLR6-1-10, ainsi que TNFAIP3 en sont des bons exemples.…”
Section: La Nature Adaptative De L'introgression Des Hominidés Archaïquesunclassified